2011
DOI: 10.1136/ard.2010.142737
|View full text |Cite
|
Sign up to set email alerts
|

High plasma leptin levels confer increased risk of atherosclerosis in women with systemic lupus erythematosus, and are associated with inflammatory oxidised lipids

Abstract: BackgroundPatients with systemic lupus erythematosus (SLE) are at increased risk of atherosclerosis, even after accounting for traditional risk factors. High levels of leptin and low levels of adiponectin are associated with both atherosclerosis and immunomodulatory functions in the general population.ObjectiveTo examine the association between these adipokines and subclinical atherosclerosis in SLE, and also with other known inflammatory biomarkers of atherosclerosis.MethodsCarotid ultrasonography was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 47 publications
9
83
0
4
Order By: Relevance
“…Although we and others have shown that leptin levels are elevated in SLE patients (5,6), it is not known whether the abnormal levels of this adipocytokine in SLE could be secondary to the chronic inflammatory state of the disease and/or directly contribute to its development.…”
mentioning
confidence: 99%
“…Although we and others have shown that leptin levels are elevated in SLE patients (5,6), it is not known whether the abnormal levels of this adipocytokine in SLE could be secondary to the chronic inflammatory state of the disease and/or directly contribute to its development.…”
mentioning
confidence: 99%
“…В ряде исследований высокие уровни лептина были связаны с риском субклинического атеросклероза у женщин [29,30].…”
Section: Discussionunclassified
“…This aspect, together with the observation that leptin concentration is abnormally elevated in autoimmune mice and in patients affected by autoimmune disease [6] , led to wonder whether certain gene polymorphisms in SLE patients could contribute to the pathogenesis of the disease [3,7] . Additionally, past studies indicated an abnormal increase in serum/plasma leptin levels in SLE patients (independent of disease activity) [8][9][10][11][12] .…”
Section: Why Leptin and Slementioning
confidence: 99%